Synthesis and Crystal Structure of One-Dimensional Zig-Zag Polymer Cadmium(II): {[Cd(μ-L)(NO3)2H2O]2H2O}n - Yang, Juan; Dong, Hua-Ze (Asian Journal of Chemistry, 2011)
A novel 1D supramolecular complex of cadmium with molecular formula {[Cd(μ-L)(NO3)2H2O]2H2O}n, was synthesized by pyridyl-pyrimidin dithioethers and Cd(NO3)2. The crystal structure of the cadmium complex, exist as the one-dimensional zig-zag polymer, showing seven-coordinate CdO5N2 distorted pentagonal dipyramid geometry. The formation of supramolecular networks structure is mainly due to intermolecular hydrogen bonding interactions between adjacent zig-zag polymers. The crystal is triclinic, space group P-1 with unit cell parameters: a = 12.231(2) Å, b = 14.349(2) Å, c = 16.022(2) Å, a = 85.731(4)º, b = 70.171(3)º, g = 79.761(4)º, V = 2602.8(6)Å3, Z = 2, Mr = 1335.90, Dc = 1.705 g/cm3, μ = 1.058 mm-1, F(000) = 1340, R = 0.0555, wR = 0.1068 for 9013 reflections with I > 2s(I).